2002
DOI: 10.1136/vr.150.25.788
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prostaglandin F and misoprostol in the induction of parturition in goats

Abstract: recovered from clinical equine ehrlichiosis were refractory to detectable re-infection and subsequent clinical disease when they were again exposed to blood infected with E equi 300 days after infection (Nyindo 1978). Equine ehrlichiosis should be differentiated from primary liver disease, purpura haemorrhagica, equine viral arteritis, encephalitis and equine infectious anaemia. In France, equine ehrlichiosis should be differentiated from equine babesiosis caused by Babesia cabali, although clinical signs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
1
18
2
Order By: Relevance
“…Although the placenta produces progesterone throughout the gestation, the corpora lutea are the major source of progesterone and must remain functional all times during pregnancy (Jarrell and Dziuk 1991; Gordon 1997). Therefore, administration of luteolytic substances could be efficiently used to terminate the pregnancy (Day and Southwell 1979) and induce parturition (Romano et al 2001; Alan and Tasal 2002) in goats.…”
Section: Introductionmentioning
confidence: 99%
“…Although the placenta produces progesterone throughout the gestation, the corpora lutea are the major source of progesterone and must remain functional all times during pregnancy (Jarrell and Dziuk 1991; Gordon 1997). Therefore, administration of luteolytic substances could be efficiently used to terminate the pregnancy (Day and Southwell 1979) and induce parturition (Romano et al 2001; Alan and Tasal 2002) in goats.…”
Section: Introductionmentioning
confidence: 99%
“…After the luprostiol injection, a fast decrease in the plasmatic progesterone concentration was observed, reaching basal levels (<1 ng/ml) at the parturition time. Different studies have related similar findings after the administration of natural PGF 2∞ (Bretzlaff and Ott 1983; Alan and Tasal 2002) or prostaglandin analogues (Batista et al. 2009).…”
Section: Discussionmentioning
confidence: 71%
“…2001; Alan and Tasal 2002) or prostaglandin analogues (Walker 1983; Haibel and Hull 1988; Alan and Tasal 2002), where the time to parturition ranged between 31 and 35 h. However, when the goats were administered with the lower dose of aglepristone (1.5 mg/kg), the interval from injection to parturition was notably higher than in other induced goats: the kidding was spread over a longer period of time and was not as predictable. Different studies have confirmed that the interval to parturition can be modified depending on the drug dose (Bretzlatt and Ott 1983; Alan and Tasal 2002); the time from injection to kidding was longer when goats were injected with low doses (2.5 mg) of natural PGF 2∞ compared to the time to parturition after the administration of 10–20 mg PGF 2∞ . For the control goats, the distribution of kidding showed a wide range, and spontaneous parturition was more difficult to accurately predict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGE 1 (oral, intravaginal or intracervical) has been used, concurrently, with parenterally administered prostaglandin‐F2 α (PGF 2 α ) to induce parturition in the doe and abortion in the bitch, respectively (Davidson et al. ; Alan and Tasal ). Similarly, intracervical PGE 2 and PGE 1 have been used in the mare to promote cervical ripening before induction of abortion or parturition (Volkmann and DeCramer ; Rigby et al.…”
Section: Introductionmentioning
confidence: 99%